Schelling and modern European philosophy : an introduction - Bowie, Andrew, 1952- (Routledge, 1993)
Bowie's book is the first introduction in English to present Schelling as a major European philosopher in his own right. It surveys the whole of his philosophical career, reconstructing his key arguments and relating them to current ideas.